Pendidikan Karakter Melalui Islamic Boarding School di SMP Plus Ar-Rahmat Bojonegoro - A. Fikri Amiruddin Ihsani; Novi Febriyanti (PAKAR Pendidikan, 2020)
This research discusses character education in the Middle School Plus Ar-Rahmat Bojonegoro. There are two issues to be discussed, how the character education process through Islamic Boarding School and how the role of each school member in character education through Islamic Boarding School. This research uses qualitative methods with descriptive analysis through observation, interview and documentation. The research showed; (1) the process of character education from within the classroom adopts the values of character education from the Ministry of Education and Culture. From outside the classroom, students are provided with religious values, good social environment, instilling disciplined and independent values, maximizing communication among students, caring for friday activities, helping fellow students, and establishing friendships. (2) the role of each school member in character education consists of; the principal acts as a role model, social control, and mobilizer. The curriculum has the role of integrating religious science and general science. The chaplain/teacher acts as a companion and an example. And students play a role in the success of character education by actively participating and raising awareness. Islamic Boarding School is present as a solution to the many new cultures that enter the era of digitalization.